2021
DOI: 10.1093/cid/ciab347
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in a Patient Transport Van

Abstract: We report 2 episodes of potential SARS-CoV-2 transmission from infected van drivers to passengers despite masking and physical distancing. Whole-genome sequencing confirmed relatedness of driver and passenger SARS-CoV-2. With the heater operating, fluorescent microspheres were transported by airflow >3 meters from the front to the back of the van.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…Frequent hand hygiene should be emphasized for patients with suspected or confirmed COVID-19. Because pre-symptomatic patients contribute substantially to transmission of SARS-CoV-2, [6][7] hand hygiene is also essential in the absence of symptoms. Educational interventions can increase hand hygiene in hospitalized patients and long-term care facility residents.…”
mentioning
confidence: 99%
“…Frequent hand hygiene should be emphasized for patients with suspected or confirmed COVID-19. Because pre-symptomatic patients contribute substantially to transmission of SARS-CoV-2, [6][7] hand hygiene is also essential in the absence of symptoms. Educational interventions can increase hand hygiene in hospitalized patients and long-term care facility residents.…”
mentioning
confidence: 99%
“…Whole-genome sequencing studies have confirmed transmission both to and from patients and healthcare workers despite one or both wearing surgical masks. 47 50 53 63 64…”
Section: Mechanisms Of Transmissionmentioning
confidence: 99%
“…57 62 In practice, this is sufficient to substantially lower infection rates, 105 106 but breakthrough transmissions despite medical or surgical masks have been well documented, in many instances using whole-genome sequencing to confirm transmission links. 47 50 53 63 90…”
Section: Maskingmentioning
confidence: 99%
“…Travel poses a substantial risk for transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other respiratory viruses because people are often required to be in close proximity for prolonged periods [1][2][3][4]. Transmission of SARS-CoV-2 has been reported on airplanes, with most secondary cases occurring in passengers sitting within a few rows of the source patient [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other situations that might place travelers at risk include crowded settings inside airports, using public transportation, staying in hotels, and eating in restaurants. Inadequate ventilation in these indoor spaces increases the risk for airborne transmission of respiratory viruses [1][2][3]. However, limited information is available on the adequacy of ventilation in many areas encountered during travel.…”
Section: Introductionmentioning
confidence: 99%